Kompetensi Dan Peran Tenaga Manajemen Informasi Kesehatan Di Rumah Sakit Sekota Denpasar Di Era Smart City - Viktorinus Alfred Saptiono; I Nyoman Mahayasa Adiputra (Jurnal Kesehatan, 2021)
nformation management is crucial In the smart city era, because the amount of information generated is abundant, approximately around five exabytes (five trillion gigabytes). According to projections from the American Health of Information Management (AHIMA) research team, there will be an increase in the amount of information by 50 times between 2012 and 2020 in the health sector. High quality health information management processes have become crucial in the Smart City era considering these increasing information productions. High quality health information management process requires competent human resources in health information management with particular skill set. This study aims to determine the initial description of the competences of health information management personnel, as well as to determine their role in health services in Denpasar city hospitals in the Smart City era.